Myokines as mediators of exercise-induced cognitive changes in older adults: protocol for a comprehensive living systematic review and meta-analysis - Vints, Wouter A. J.; Gökçe, Evrim; Langeard, Antoine; Pavlova, Iuliia; Çevik, Özge Selin; Ziaaldini, Mohammad Mosaferi; Todri, Jasemin; Lena, Orges; Sakkas, Giorgos K.; Jak, Suzanne; Zorba (Zormpa), Ioanna; Karatzaferi, Christina; et al. (Frontiers in Aging Neuroscience, 2023)
Background The world’s population is aging, but life expectancy has risen more than healthy life expectancy (HALE). With respect to brain and cognition, the prevalence of neurodegenerative disorders increases with age, affecting health and quality of life, and imposing significant healthcare costs. Although the effects of physical exercise on cognition in advanced age have been widely explored, in-depth fundamental knowledge of the underlying mechanisms of the exercise-induced cognitive improvements is lacking. Recent research suggests that myokines, factors released into the blood circulation by contracting skeletal muscle, may play a role in mediating the beneficial effect of exercise on cognition. Our goal in this ongoing (living) review is to continuously map the rapidly accumulating knowledge on pathways between acute or chronic exercise-induced myokines and cognitive domains enhanced by exercise. Method Randomized controlled studies will be systematically collected at baseline and every 6 months for at least 5 years. Literature search will be performed online in PubMed, EMBASE, PsycINFO, Web of Science, SportDiscus, LILACS, IBECS, CINAHL, SCOPUS, ICTRP, and ClinicalTrials.gov. Risk of bias will be assessed using the Revised Cochrane Risk of Bias tool (ROB 2). A random effects meta-analysis with mediation analysis using meta-analytic structural equation modeling (MASEM) will be performed. The primary research question is to what extent exercise-induced myokines serve as mediators of cognitive function. Secondarily, the pooled effect size of specific exercise characteristics (e.g., mode of exercise) or specific older adults’ populations (e.g., cognitively impaired) on the relationship between exercise, myokines, and cognition will be assessed. The review protocol was registered in PROSPERO (CRD42023416996). Discussion Understanding the triad relationship between exercise, myokines and cognition will expand the knowledge on multiple integrated network systems communicating between skeletal muscles and other organs such as the brain, thus mediating the beneficial effects of exercise on health and performance. It may also have practical implications, e.g., if a certain myokine is found to be a mediator between exercise and cognition, the optimal exercise characteristics for inducing this myokine can be prescribed. The living review is expected to improve our state of knowledge and refine exercise regimes for enhancing cognitive functioning in diverse older adults’ populations. Registration Systematic review and meta-analysis protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO) on the 24th of April 2023 (registration number CRD42023416996).